PELATIHAN COPYWRITING SEDERHANA UNTUK PEMULA DI SMK TRIGUNA JAKARTA SELATAN - Jundrio, Harry; Ardiansyah, Ardiansyah; Tungga Dewi, Indira Tribhuwana; Utami, Rahmi; Andri, Shalfi (JURNAL ABDIMAS PLJ, 2025)
This community service activity aims to equip students of SMK Triguna 1956, Petukangan Utara, Pesanggrahan, South Jakarta to enter the world of work. This community service activity is packaged in the form of training with the theme of digital marketing. Specifically, the theme focuses on simple copywriting techniques in creating product advertisements. The training participants are grade X students. In general, the training participants have been able to understand the concept of marketing in general well, including the definition and advantages and disadvantages of digital marketing. However, the training participants have not been able to understand how to create headlines or content titles that attract attention in advertising products to consumers. By participating in this training, participants are expected to be able to apply digital marketing tools in general, both in companies and for their own businesses. In addition, participants are expected to be able to implement simple copywriting techniques in communicating product value to consumers. The implementation of this community service activity was carried out thanks to the collaboration with the Institute for Research and Community Service (LPPM) of Tempo Polytechnic which was supported by representatives of Tempo Polytechnic students from the International Marketing Management Study Program.